Utility of fertility procedures and prenatal tests to estimate gestational age for live‐births and stillbirths in electronic health plan databases. Issue 5 (22nd February 2022) - Taylor, Lockwood G.; Bird, Steven T.; Stojanovic, Danijela; Toh, Sengwee; Maro, Judith C.; Fazio‐Eynullayeva, Elnara; Petrone, Andrew B.; Rajbhandari, Rajani; Andrade, Susan E.; Haynes, Kevin; McMahill‐Walraven, Cheryl N.; Shinde, Mayura; et al.
Abstract: Purpose: Current algorithms to evaluate gestational age (GA) during pregnancy rely on hospital coding at delivery and are not applicable to non‐live births. We developed an algorithm using fertility procedures and fertility tests, without relying on delivery coding, to develop a novel GA algorithm in live‐births and stillbirths. Methods: Three pregnancy cohorts were identified from 16 health‐plans in the Sentinel System: 1) hospital admissions for live‐birth, 2) hospital admissions for stillbirth, and 3) medical chart‐confirmed stillbirths. Fertility procedures and prenatal tests, recommended within specific GA windows were evaluated for inclusion in our GA algorithm. Our GA algorithm was developed against a validated delivery‐based GA algorithm in live‐births, implemented within a sample of chart‐confirmed stillbirths, and compared to national estimates of GA at stillbirth. Results: Our algorithm, including fertility procedures and 11 prenatal tests, assigned a GA at delivery to 97.9% of live‐births and 92.6% of stillbirths. For live‐births ( n = 4 701 207), it estimated GA within 2 weeks of a reference delivery‐based GA algorithm in 82.5% of pregnancies, with a mean difference of 3.7 days. In chart‐confirmed stillbirths ( n = 49), it estimated GA within 2 weeks of the clinically recorded GA at delivery for 80% of pregnancies, with a mean difference of 11.1 days. Implementation of the algorithm in a cohort of stillbirths ( n = 40 484) had an increased percentage of deliveries after 36 weeks compared to national estimates. Conclusions: In a population of primarily commercially‐insured pregnant women, fertility procedures and prenatal tests can estimate GA with sufficient sensitivity and accuracy for utility in pregnancy studies.